The demand for mortgage debt, increases in house prices and the elderly home equity puzzle - Jan Rouwendal; Marcus de Graaf (European Regional Science Association (ERSA), 2012)
This paper studies the demand for mortgage debt in the Netherlands. Currently the size of this debt exceeds that of GDP, which makes is interesting to look at its determinants. We argue that the absence of a downpayment constraint is important and focus on two other issue. The first is the impact of the prolonged boom in house prices in the period 1985-2005, which makes it interesting to investigate how much of this increase in housing wealth has been `cashed' by households. The second is the elderly home equity puzzle,' or the habit of elderly people to leave their housing wealth untouched when aging. Recent analyses for the US have suggested that this behavior may be caused by the combination of a strong precautionary savings motive and a high risk of large health care costs. However, in the Netherlands long term care is publicly financed, which makes this explanation unlikely to be valid. It is therefore interesting to see if Dutch households liquefy substantial parts of their housing wealth by increasing the size of the mortgage loan.
Keywords: 330